Exposure of Portuguese population to aflatoxins: the contribution of human biomonitoring to estimation of burden of disease - Martins, Carla (2020)
Human biomonitoring (HBM) is recognized as an important tool to assess the Human exposure to chemicals, contributing to describe trends and patterns of exposure over time and to identify population groups that could be under risk. Natural chemicals as mycotoxins, fungi metabolites that produce toxic effects in humans, are important compounds that could be found in foods usually consumed worldwide in a daily basis. Mycotoxins as aflatoxins (AFTs) are genotoxic, carcinogenic and immunosuppressive compounds. Hepatocellular carcinoma (HCC) is one of their main health toxic effects and is the third leading cause of cancer deaths worldwide. In Portugal, scarce data are available regarding exposure to AFTs and none previous study used HBM data to characterize comprehensively the burden associated to this exposure. In the scope of the National Food, Nutrition, and Physical Activity Survey of the Portuguese General Population (2015-2016), 24h-urine samples from 94 participants were analyzed by liquid chromatography–mass spectrometry (LC-MS/MS) for the simultaneous determination of AFTs (B1, B2, G1, G2, M1). A model was developed to estimate the health impact of the exposure of Portuguese population to aflatoxins, estimating the number of cases of HCC and DALYs attributed to AFTs exposure. AFTs were detected in 12.8% (AFB1), 16.0% (AFB2) and 19.1% (AFM1) of the 24h-urine samples. The estimated number of extra cases of HCC attributed to this exposure ranged from 17 to 65 cases/year; the associated DALYs for the Portuguese population ranged from 284 to 1802 years. The present study generated, for the first time and within a HBM study, reliable data on internal exposure to AFTs at individual level for the Portuguese population. These data were crucial to characterize the burden derived from this exposure and to support risk managers to establish preventive policy measures that contribute to ensure the public health protection.